Analisis Dan Perancangan Sistem Informasi Inventarisasi Barang Berbasis Web Pada Badan Keuangan Daerah Provinsi Jambi - Rinaldo, Jimmy; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
The process of inventory at the Local Government Finance Office of Jambi Province still uses Microsoft Excel and inventory books, resulting in a slow process of reporting inventory items. The purpose of this research is to design a web-based inventory information system in accordance with the needs of the Local Government Finance Office of Jambi Province, with the inventory website of the Local Government Finance Office of Jambi Province can be easier in terms of inventory information. Designing a Web-Based Goods Inventory System at the Local Government Finance Office of Jambi Province uses object-based modeling techniques to illustrate system analysis and design, namely in the form of use case diagrams, activity diagrams, and class diagrams. The output of this research is in the form of a prototype design of the Analysis System and the Design of a Web-Based Inventory System at the Local Government Finance Office of Jambi Province. Suggestions for further research in order to complement the management of other data, such as requests for item, lost item reports and data security.